AB0168 Elevated serum levels of hmgb1 and srage in patients with antiphospholipid syndrome. (12th June 2018) - Truglia, S.; Manganelli, V.; Capozzi, A.; Alessandri, C.; Lococo, E.; Garofalo, T.; Sorice, M.; Longo, A.; Misasi, R.; Conti, F.; Valesini, G.
Abstract : Background: Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterised by the presence of at least one clinical event among vascular thrombosis and/or pregnancy morbidity, in the presence of circulating antiphospholipid antibodies (aPL). High-mobility group box-1 (HMGB1) is a non-histonic protein belonging to the family of alarmins. It is associated with chromatin and has a dual function depending on the cell state: in basal conditions it is located in the nucleus and promotes the interaction of some transcription factors with DNA, in inflammatory conditions it is secreted in the extracellular space and exerts the functions of a pro-inflammatory cytokine. One of the main receptor system responsible for the HMGB1 activity is the "receptor for advanced glycation end products" (RAGE). Increased serum HMGB1 levels have been reported in patients with Systemic Lupus Erythematosus and pre-eclampsia, as other alarmins are increased in patients with early abortions. Objectives: To evaluate the serum levels of HMGB1 and soluble RAGE (sRAGE) in patients with obstetric and thrombotic APS. Methods: 43 consecutive patients with APS, diagnosed according to the Sapporo criteria, were enrolled. The study cohort included both primary APS (=15) and APS associated with SLE (=28). In addition, 30 healthy subjects (HC) matched for age and sex were studied as controls. Serum levels of HMGB1 and sRAGE were analysed by Western blot. Results: The clinical features of the enrolled patients (40 females and 3 males, mean age 40.98±13.48 years, ) are reported in table 1. HMGB1 and sRAGE serum levels were significantly increased in APS patients in comparison with controls (p<0.001) (figure 1). Furthermore, no difference in HMGB1serum leved were detected among patients with thrombotic or obstetric APS and patients with primary or secondary APS.APS patients with thrombosis showed higher levels of HMGB1 than APS patients without thrombosis; in addition, in APS patients there is a correlation between HMGB1 serum levels and thrombosis. Conclusions: In this study, we investigated for the first time the serum levels of HMGB1 and sRAGE in patients with APS, showing increased levels in both primary and secondary APS compared to controls. Larger studies are needed to assess whether monitoring serum HMGB1/sRAGE levels could be a useful tool for risk stratification in patients with APS. Disclosure of Interest: None declared